Invisible medicine sellers and their use of antibiotics: a qualitative study in Cambodia. Issue 5 (September 2019) - Suy, Sovanthida; Rego, Sonia; Bory, Sothavireak; Chhorn, Sophea; Phou, Socheata; Prien, Chanra; Heng, Sotheara; Wu, Shishi; Legido-Quigley, Helena; Hanefeld, Johanna; Saphonn, Vonthanak; Khan, Mishal S
Abstract : Background: Global attention to antimicrobial resistance has increased interest in tackling the widespread inappropriate dispensing of antibiotics by informal, for-profit healthcare providers (HCPs). We provide new evidence on an understudied group of informal HCPs: invisible medicine sellers (IMS) who operate without any marked facility. We investigated factors that influence community decisions on which HCPs to purchase medicines from, focusing on reasons for using IMS, and compared different HCPs' knowledge of antibiotic use. Methods: We conducted community focus group discussions (FGDs) in seven purposively selected villages representing high and low informal HCPs use in two peri-urban districts in Phnom Penh, Cambodia. Using information from the FGDs to identify HCPs that sell medicines, we interviewed 35 participants: 21 HCPs (including five IMS) and 14 key informants, including government HCPs and village leaders. We adopted an interpretative approach and conducted a thematic analysis. Results: Community members typically knew of several formal and informal HCPs selling medicines nearby, and IMS were common, as were doctors that sell medicines covertly. Two factors were most salient in influencing the choice of HCP for medicine purchasing. The first was trust in the effectiveness of medicines provided, judged by the speed of symptomatic relief. This pushed HCPs to provide several medicines, including antibiotics, at the first consultation. The second was the convenience offered by IMS and other informal HCPs: supplying medicines when other facilities are closed, accepting delayed payments, providing incomplete courses of medication and selling human antibiotics for animal use. Conclusion: This first study focusing on IMS indicates that it is important, but challenging, for public health agencies to engage with them to reduce inappropriate use of antibiotics. Although public health facilities must fill some gaps that informal HCPs are currently addressing, such as access to medicines at night, reducing demand for unnecessary antibiotics is also critical.